Doing research on 'sensitive topics': Studying the Sweden-South Africa Arms Deal - Coetzee, Wayne Stephen (Scientia Militaria - South African Journal of Military Studies, 2020)
The conventional arms trade is a sensitive topic that is often shrouded in secrecy. As with most aspects of so-called ‘high politics’, processes connected to conventional arms trade habitually take place behind closed doors between a relatively small and tightly knit group of individuals. Gaining access to such people is an enormous challenge for any researcher. Moreover, building rapport with key decision-makers takes a long time, and it requires considerable effort and resolve. This article recapitulates the approach and method of a study done on conventional Swedish arms trade with South Africa. It provides insights into several substantive issues related to such research, in particular, aspects connected to elite interviewing and research ethics. The bulk of the article covers matters related to research design, access to elites, the limitations associated with elite interviewing, and the interview process that was adopted during fieldwork.  The discussion on research ethics is closely, but not exclusively, connected to elite interviewing, and here the article reflects on various ethical considerations as well as the harsh reality of researching sensitive topics, such as conventional arms trade.